Fibroids of the Uterus and Outcome of Pregnancy (Medical Forum Monthly, 2024)
Objectives: To study the outcome of pregnancy in Fibroids of the Uterus.Design of Study: Prospective / Experimental Study.Place and Duration of Study: This study was conducted at the Idris Teaching Hospital, Sialkot & Islam Teaching Hospital, Sialkot from August 2013 to August 2016.Materials and Methods: This study was carried to seek out the result of maternity related to female internal reproductive organ fibroids and to find out the actual fact that each pregnant female should be screened for female internal reproductive organ fibroids (UF). If the fibroids diagnosed along with pregnancy, these patients want alert prenatal care and therefore the maternity ought to be treated as high risk maternity. Fifty pregnant females with fibroids of the uterus were enrolled during this Prospective Experimental Study. Performa was designed to record age, socio economic standing, area, complications in early, late maternity and delivery. Written informed consent was taken from every patient. Permission was additionally taken from ethical committee of the institutes. The data was analyzed on SPSS version ten for results. Results: In this study it was observed that incidence of pregnancy with fibroids uterus was higher(54%) n=27 at the age of 31-35 years as compared to other age groups. The women of middle socio economic group had higher incidence of pregnancy with Fibroids of the Uterus (46%) n=23 as compared to other socio economic group of women. The women from rural areas had double incidence of pregnancy with Fibroids of the Uterus (68%) n=34 as compared to women having pregnancy with Fibroids of the Uterus from urban areas (32%) n=16. The incidence of miscarriage of pregnancy with Fibroids of the Uterus was maximum (28%) n=14 and patients of fetal growth restriction was minimum (04%)n=02 in complications of pregnancy. The incidence of Postpartum hemorrhage was maximum (46%) n=23 and minimum (08%) n=04 in case of retained placenta during delivery.